Pendeteksian Fraudulent Financial Statement: Pengujian Fraud Heptagon Theory - Siti Azizah; Reskino Reskino (Universitas Muhammadiyah Jakarta, 2023)
Objectives. This study aims to examine Reskino's (2022) heptagon fraud theory, which encompasses seven dimensions: pressure, opportunity, rationalization, competence, arrogance, culture, and religiosity.Design/method/approach. Data was collected through purposive sampling, wherein questionnaires were distributed to auditors in DKI Jakarta. A total of 117 respondents completed the questionnaires, and subsequently analyzed using SEM-PLS.Result/findings. The results show that pressure, opportunity, rationalization, and competence do not have a significant impact on detecting fraudulent financial statements. On the other hand, arrogance, culture, and religiosity are revealed to exert a strong influence in this regard.Theoretical contribution. This study represents the inaugural examination of the most recent fraud theory, known as the fraud heptagon theory, formulated by Reskino (2022). The primary aim is to address the existing gap in the literature, which lacks an explanation for fraud occurrences attributed to religious and cultural factors.Practical contribution. The anticipated outcome of this research is to provide valuable insights that could serve as input for regulators in formulating regulations that consider the influence of religion and culture.Limitations. This study solely relies on primary data gathered from the perspectives of auditors operating in the DKI Jakarta region. Consequently, the research scope is limited, making it inappropriate to generalize the findings to auditors outside the DKI Jakarta area.